Optimizing the modulation paradigm of transcutaneous auricular vagus nerve stimulation in patients with disorders of consciousness: A prospective exploratory pilot study protocol - Zhai, Weihang; Jiao, Haoyang; Zhuang, Yutong; Yang, Yi; Zhang, Jinling; Wang, Yifei; Wang, Yu; Zhao, Ya-nan; Zhang, Shuai; He, Jianghong; Rong, Peijing (Frontiers in Neuroscience, 2023)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive neuromodulation technique. Several studies have reported the effectiveness of taVNS in patients with disorders of consciousness (DOC); however, differences in the modulation paradigm have led to inconsistent treatment outcomes. Methods/design This prospective exploratory trial will include 15 patients with a minimally conscious state (MCS) recruited according to the coma recovery scale-revised (CRS-R). Each patient will receive 5 different frequencies of taVNS (1, 10, 25, 50, and 100 Hz); sham stimulation will be used as a blank control. The order of stimulation will be randomized, and the patients’ CRS-R scores and resting electroencephalography (EEG) before and after stimulation will be recorded. Discussion The overall study of taVNS used in treating patients with DOC is still in the preliminary stage of exploration. Through this experiment, we aim to explore the optimal stimulation frequency parameters of taVNS for the treatment of DOC patients. Furthermore, we expect to achieve a stable improvement of consciousness in DOC patients by continuously optimizing the neuromodulation paradigm of taVNS for the treatment of DOC patients. Clinical trial registration https://www.chictr.org.cn/index.aspx, identifier ChiCTR 2200063828.